Microsatellite Markers Reveal Genetic Diversity and Population Structure of Village Chicken in Peninsular Malaysia (Early view) - Zulkifli; Shairah Abdul Razak, Amie Marini Abu Bakar, Shahril Ab Razak, Siti Norhayati Ismail, Lim Wen Hui, Azlina Azma Ismail Affendee, Roziatul Erin Abdul Razak, Nooraisyah Saharani, Mohd Hafizzudin Ayob, Mohd Firdaus Othman, Noraini Samat, Mohd Hishammfariz Mohd Amin, Nadiatur Akma (Tropical Life Sciences Research, 2026)
The emphasis on high-yield poultry breeds has contributed to the decline and underutilisation of indigenous chickens. In Malaysia, the “kampung chicken” or Malaysian Village Chicken (MVC) is often viewed as low in productivity, yet it remains culturally important and is well adapted to local environments, making it a valuable resource for sustainable poultry production. As selective breeding and improvement efforts such as the development of the dual-purpose Saga chicken – expand, comprehensive genetic characterisation of MVC is essential to safeguard native diversity, guide future breeding strategies and prevent genetic erosion. This study aimed to ascertain the genetic diversity of MVC ecotypes across Peninsular Malaysia and examine their genetic relationships with commercial and jungle fowl breeds using simple sequence repeat (SSR) markers. Fifteen village chicken ecotypes, including Saga chicken, were sampled from multiple regions, together with four commercial breeds (Cobb, Ross, Sasso and Hy-Line) and jungle fowl chickens. Twenty SSR markers were used, of which 17 polymorphic markers successfully amplified. Cluster analyses using UPGMA and Neighbour-Joining dendrograms revealed two major genetic groups. MVC formed a distinct lineage separate from commercial breeds and further segregated into three subclusters reflecting geographical origins. Although Sasso broilers resemble MVC phenotypically, SSR analysis confirmed clear genetic differentiation. These finding underscore the unique genetic structure of Malaysian Village Chickens, which likely supports their adaptability to tropical regions and efficient utilisation of local feed resources. The findings provide a strong foundation for conservation planning, genetic resource management and the strategic optimisation of future breeding programmes.